HALAQOH AS A LEARNING SYSTEM IN DEVELOPING ACADEMIC SPIRITUAL COMPETENCIES STUDENTS AT DARUL FIQHI LAMONGAN ISLAMIC BOARDING SCHOOL - M Yunus; Nur Hakim; Mita Nur Fatmawati; Djuwairiyah Djuwairiyah (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2024)
Halaqoh is a learning system that has an important role to play in the development of academic and spiritual competence in the darul fiqhi boarding house. In the abstract, it will be discussed the significance, methods, and results of the implementation of halaqoh in the boarding school. Halaqoh is a religious discussion forum that is held regularly in boarding schools, where santri gathers to discuss religious issues, to understand religious texts, and to explore spiritual values. These methods of learning enable santri to interact directly with educators and fellow santri, facilitate a deep understanding of islamic doctrine, and promote moral and ethical values. The implementation of halaqoh has had a positive impact on the development of academic and spiritual competence in the darul fiqhi boarding house. Santri became more adept at learning religious teachings, improved in speaking and discussion skills, and integrated religious values into everyday life. The result was that santri not only excelled in academic aspects, but also had strong spiritual depth. In the context of islamic education, halaqoh in the darul fiqhi boarding house became a successful model of blending academic and spiritual education. It provides a solid foundation for santri to be a competent and ethical leader in society, and it makes the boarding school an educational institution that contributes to the formation of a faithful and knowledgeable generation.